Respuesta :

Answer:

(4,4)

Step-by-step explanation:

Let us assume A has coordinates (-3,1)

We were given that the midpoint of AC is (0.5,2.5).

Let the coordinates of C be (a,b) then by the midpoint theorem;

[tex](\frac{a+-3}{2},\frac{b+1}{2})=(0.5,2.5)[/tex]

Then:

[tex]\frac{a-3}{2}=0.5[/tex]  and [tex](\frac{b+1}{2}=2.5[/tex]

[tex]\implies a-3=1[/tex]  and [tex]b+1=5[/tex]

[tex]\implies a=1+3[/tex]  and [tex]b=5-1[/tex]

[tex]\implies a=4[/tex]  and [tex]b=4[/tex]

Therefore C has coordinates: (4,4)

ACCESS MORE